Alternative Conception of Art History Course in Professional Higher Education Study Programmes - Jermolajeva, Jelena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Cultural environment becoming increasingly visualized, humanitarians and professionals in socio-cultural sphere should adequately read, analyze, and effectively use various visual objects. Therefore many professional higher education study programmes include an Art History Course. The paper criticizes the traditional chronological/regional approach to the structuring of this Course. The aim of the study is to propound an alternative approach, where the historical art process is regarded as coexistence of and interaction between the six Main Art Trends, each of them developing from the ancient times to the present days. The paper discusses the advantages of this approach. The study draws upon the conceptions of art styles developed by F. Niezsche, D. Cizevsky, M. Lotman and some other philosophers and culturologists of the 19th–20th centuries.